Análisis comparativo de los docentes investigadores universitarios de la zona 7 – sur del Ecuador y su incursión en las redes sociales científicas - Benitez Arrobo, Karen Michelle (2020)
In the present work, the presence of university research professors from the Faculties of Social Sciences and Socio-Humanistic Area of the universities belonging to Zone 7 - South of Ecuador, Universidad Técnica Particular de Loja (UTPL), Universidad Técnica is analyzed in a comparative way. de Machala (UTMACH) and Universidad Nacional de Loja (UNL), in the academic scientific networks: ResearchGate, Academia.edu, and the Google Scholar platform. With a total of 240 identified teachers and with the use of observation cards, the level of presence of each of them in the academic scientific networks of study was determined. By identifying the number of visits, the number of citations they have in each of their profiles, the RS Score index is also determined in the case of ResearchGate and the h index in the Google Scholar platform, this in order to measure the impact that academic publications have when they are published through academic scientific networks. And it is complemented by interviews with people related to research, digital communication and use of digital social networks. The results show that the use of scientific social networks by university research professors from Zone 7- South of Ecuador is still in the process of consolidation. At the same time that the respondents state that being present on academic social networks results in greater visibility of scientific production at the local, national and international level, becoming an effective way for the dissemination of science. Keyworsds: Social Media; Academic networks; Science popularization; Universities of Zone 7 – South of Ecuador and scientific investigation.